Aqidah, Syariah, dan Akhlak: Pilar Utama Pembentukan Karakter Muslim - Alyanisa Thalita; Halimatus Sa’diah; Rokhilawati; M. Yusuf Bahtiar (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study examines the contribution of Aqidah, Sharia, and Morals to the formation of Muslim character. Aqidah serves as the foundation of faith, Sharia serves as a guideline for regulating daily behavior, while Morals are the manifestation of ethical behavior reflected in social life. These three components are interrelated and together form a balanced Muslim personality. The approach and method used in this study were qualitative, using a literature review method obtained through theories of Islamic education, character formation, and moral development from various books and scientific journals. The collected data were then subjected to further analysis. The results of the study indicate that the integration of Aqidah, Sharia, and Morals plays a role in shaping individuals with strong spiritual awareness, commendable behavior, and social responsibility. Individuals who possess strong Aqidah, consistently adhere to Sharia, and practice good Morals tend to demonstrate honesty, discipline, and empathy in social life. Furthermore, character education based on Islamic values ​​can also strengthen moral awareness and create harmonious social relationships. The implications of this research suggest that both formal and non-formal educational institutions need to integrate faith values, religious practices, and morals into character education programs. This integration is expected to produce a generation with integrity, religious character, and the ability to adapt to the challenges of the modern era.